Pembinaan model 1sekolah: Ke arah merealisasikan konsep 1Malaysia dan Pendidikan multi budaya dalam abad ke 21 - Mohd Yusof, Zailani; Mohd Yusof, Fahainis; Md Ali, Ruzlan; Raman, Arumugam; Othman, Abu Hassan; Samsuddin, Shuhaili (Universiti Utara Malaysia, 2014)
This study aims to build a 1 Malaysia School Model cultural diversity among students to promote racial integration.This study is to see significant differences between the various cultures based on race, gender, age, teaching experience and highest academic qualification. The sample refer to multicultural education either within or outside the country, officers in the Ministry of Education, headmasters, senior assistants and teachers Vision School. Demographic factor is composed of gender.Results of the t-test inferential analysis found that there were significant differences between the various cultures according to race, gender, age, teaching experience and highest academic qualification. While through the qualitative analysis of the results found the most respondents are given positive responded of multicultural education for racial integration in Malaysia.